Normative Problems in Settlement of Waste Disputes in Court According to Law Number 18 of 2008 concerning Waste Management - Risang Pujiyanto; RB Seno Wulung; Sonny Taufan (Universitas Kuningan, 2022)
Garbage is something that will always grow along with the rate of population growth. If waste is not managed properly, it will become a problem that often leads to disputes. Dispute resolution regarding waste management is currently regulated in Law Number 18 of 2008 concerning Waste Management, but the norms governing it are still unclear. This research is a type of normative research that is carried out using a statutory approach. The results of the research show that Law Number 18 of 2008 concerning Waste Management does not clearly define Waste Management as one of the parties to a dispute in waste management. This is contrary to the Principle of Clarity of Formula contained in Law Number 12 of 2011 concerning Formation of Legislation as last amended by Law Number 13 of 2022 concerning the Second Amendment to Law Number 12 of 2011 concerning Formation of Legislation invitation. The unclear definition of Waste Management can ultimately result in legal certainty in waste disputes.